2016
DOI: 10.1038/ncomms11763
|View full text |Cite
|
Sign up to set email alerts
|

Sub-micrometre accurate free-form optics by three-dimensional printing on single-mode fibres

Abstract: Micro-optics are widely used in numerous applications, such as beam shaping, collimation, focusing and imaging. We use femtosecond 3D printing to manufacture free-form micro-optical elements. Our method gives sub-micrometre accuracy so that direct manufacturing even on single-mode fibres is possible. We demonstrate the potential of our method by writing different collimation optics, toric lenses, free-form surfaces with polynomials of up to 10th order for intensity beam shaping, as well as chiral photonic crys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
175
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 292 publications
(175 citation statements)
references
References 59 publications
0
175
0
Order By: Relevance
“…Since the sol-gel route is open to mixing different oxide precursors and concentrations, this opens up the capability of creating the different refractive index PI-free optical elements required for aberration control in multi-component lens optical systems [44,59,60,61]. With pyrolysis, an even larger range of refractive index tunability is accessible.…”
Section: Discussionmentioning
confidence: 99%
“…Since the sol-gel route is open to mixing different oxide precursors and concentrations, this opens up the capability of creating the different refractive index PI-free optical elements required for aberration control in multi-component lens optical systems [44,59,60,61]. With pyrolysis, an even larger range of refractive index tunability is accessible.…”
Section: Discussionmentioning
confidence: 99%
“…In the second fabrication step, a commercially available Nanoscribe 3D laser writer is used. The sample is first drop coated with resist, which is exposed to the desired hemispherical geometry with submicrometric writing resolution27. An example of the final structure is shown in the microscope picture in Fig.…”
Section: Methodsmentioning
confidence: 99%
“…To date, only direct laser writing based 3DLL was shown to be capable of true 3D manufacture at the microscale. This additive manufacturing technique [35] combines a complete freedom of architecture of produced structures [36], possibility to integrate it on various substrates [37][38][39] and a large range of materials that can be processed in such fashion [40]. Here we have shown that structures produced out of zirconium containing photopolymer SZ2080 can withstand a relatively low intensity I = 86.6 W/cm 2 short wavelength exposure for prolonged time periods.…”
Section: Discussionmentioning
confidence: 83%
“…Composition control of sol-gel resists via different portions of organic and inorganic components provides a tool to tune refractive index and to create complex micro-optical elements for high quality optical imaging as compared with only shape control of composite lenses [38]. With pyrolysis, an even larger range of refractive index tunability is accessible.…”
Section: Discussionmentioning
confidence: 99%